Identification of integrin α3 as a molecular marker of cells undergoing epithelial–mesenchymal transition and of cancer cells with aggressive phenotypes. Issue 9 (20th July 2013) - Shirakihara, Takuya; Kawasaki, Tomonori; Fukagawa, Akihiko; Semba, Kentaro; Sakai, Ryuichi; Miyazono, Kohei; Miyazawa, Keiji; Saitoh, Masao
<x xml:space="preserve">Abstract</x> Epithelial–mesenchymal transition (EMT) is a crucial event in wound healing, tissue repair, and cancer progression in adult tissues. Transforming growth factor (TGF)‐β induces EMT in mouse epithelial cells. During prolonged treatment, TGF‐β successively induces myofibroblastic differentiation with increased expression of myofibroblast marker proteins, including smooth muscle α actin and calponin. We recently showed that fibroblast growth factor‐2 prevented myofibroblastic differentiation induced by TGF‐β, and transdifferentiated the cells to those with much more aggressive characteristics (enhanced EMT). To identify the molecular markers specifically expressed in cells undergoing enhanced EMT induced by the combination of TGF‐β and fibroblast growth factor‐2, we carried out a microarray‐based analysis and found that integrin α3 (ITGA3) and Ret were upregulated. Intriguingly, ITGA3 was also overexpressed in breast cancer cells with aggressive phenotypes and its expression was correlated with that of δEF‐1, a key regulator of EMT. Moreover, the expression of both genes was downregulated by U0126, a MEK 1/2 inhibitor. Therefore, ITGA3 is a potential marker protein for cells undergoing enhanced EMT and for cancer cells with aggressive phenotypes, which is positively regulated by δEF‐1 and the MEK–ERK pathway.